INNOVATIVE APPROACHES IN THE EARLY DETECTION AND MANAGEMENT OF CORONARY ARTERY DISEASE - Majidova Odilaxon Zarif qizi; Usmonova Xilola Sayfulla qizi; Shermatova Zuhra Raxmatovna; Yunisova Solixa Ibragimovna (Modern American Journals, 2025)
Coronary artery disease (CAD) remains a leading cause of morbidity and mortality worldwide. Early detection and effective management are critical to improving patient outcomes and reducing healthcare burdens. This article explores the latest innovative approaches in diagnosing and treating CAD, including advancements in biomarker identification, non-invasive imaging technologies, and the application of artificial intelligence in risk stratification. Additionally, emerging therapeutic strategies such as personalized medicine and novel pharmacological agents are discussed. By integrating cutting-edge diagnostic tools with tailored management plans, healthcare providers can enhance early intervention, prevent disease progression, and improve quality of life for patients with CAD. This review highlights the potential of these innovations to transform clinical practice and offers insights into future research directions.
Keywords: Coronary artery disease (cad), early detection, non-invasive imaging, biomarkers, artificial intelligence (ai), risk stratification, personalized medicine, pharmacological therapies, cardiovascular diagnosis, disease management, preventive cardiology, novel treatment strategies.